2007
DOI: 10.1590/s0034-70942007000100011
|View full text |Cite
|
Sign up to set email alerts
|

Dor: aspectos atuais da sensibilização periférica e central

Abstract: Tissue and neuronal lesions result in sensitization of the nociceptors and facilitation of the central and peripheral nervous conduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
44

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 26 publications
(66 reference statements)
0
36
0
44
Order By: Relevance
“…Its manifestation is different and unique for each individual because each one has an individual perception about pain. In addition, pain is associated to physical and psychic factors 3 . Pain is a symptom and one of the most frequent reasons for looking for medical aid 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Its manifestation is different and unique for each individual because each one has an individual perception about pain. In addition, pain is associated to physical and psychic factors 3 . Pain is a symptom and one of the most frequent reasons for looking for medical aid 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It is present in over 70% of patients who seek medical care for various reasons in Brazil (2). Langley et al (3), in their study with a sample of Spanish subjects, found a strong association between the symptom of pain and the reduction in the workforce, absenteeism and presenteeism, demonstrating the great socio-economic impact of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…In pain stimulus presence despites chemical, thermic or mechanical occurred algiogenic substances releases such as bradicinines, acetylcoline, serotonine, histamine and prostaglandines. Such substances unleash process that results in reduction of action potential limiar of nociceptors (15,16).…”
Section: Introductionmentioning
confidence: 99%